2009
DOI: 10.1089/end.2009.0377
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Partial Nephrectomy Versus Laparoscopic Partial Nephrectomy: Comparison of Outcomes

Abstract: In this pilot study, we found that RAPN and LPN are feasible and safe operations in T1 renal tumors. The advantages for RAPN are excision of the tumor under three-dimensional vision and easy suturing with the articulated instruments of the robotic system. The cost and the need for two experienced laparoscopic surgeons are the disadvantages of robotic surgery. Larger randomized studies are needed to evaluate whether RAPN has any advantages over LPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 33 publications
1
61
0
1
Order By: Relevance
“…Our findings with respect to operative times (195 mins), and amounts of bleeding (and 250 mL) were generally in line with the findings in the medical literature. [1,11,18,19] We believe that our patients did not require blood transfusion because of effective and easy closure of the ports with the suture advantages of RAPN. Generalized subcutaneous ecchymosis that was observed in three of our patients in the postoperative period originated from the nearly lateral ports.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our findings with respect to operative times (195 mins), and amounts of bleeding (and 250 mL) were generally in line with the findings in the medical literature. [1,11,18,19] We believe that our patients did not require blood transfusion because of effective and easy closure of the ports with the suture advantages of RAPN. Generalized subcutaneous ecchymosis that was observed in three of our patients in the postoperative period originated from the nearly lateral ports.…”
Section: Discussionmentioning
confidence: 85%
“…In the same study, the authors also reported that the mean duration of operation was 185 (120-170) minutes and the amount of bleeding was 286 ml for RAPN. [19] In general, it is observed that RAPN is more advantageous compared to LPN with respect to warm ischemia time. Warm ischemia time is important for reserving renal functions and Mir et al [3] reported that the preoperative renal functions and parenchymal volume preservation are important for ultimate function after PN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Minimally invasive surgery is increasingly being applied in the management of adrenal and renal masses, including laparoscopic [3][4][5][6][7] and robot-assisted laparoscopic approaches. [8][9][10][11][12][13][14][15] Here we present a challenging case of synchronously detected right adrenal and left renal masses resected via sequential robotic right adrenalectomy and zero ischemia off-clamp left partial nephrectomy.…”
Section: Introductionmentioning
confidence: 99%